Biological aspects of modern dental composites - Jan Tore Samuelsen; Jon E. Dahl (Medical Journals Sweden, 2023)
AbstractBiological evaluation of resin-based dental composites has traditionally been based on in vitro endpoint tests with different methods to determine loss of cell viability and cell morphology changes after exposure to the material or monomer constituents. The data reveals a potential for biological effects, but clinical relevance of such data is limited. Positive allergy tests and allergic clinical reactions to dental monomers are observed in dental personnel and patients. The aim of this review is to address newer research on molecular events caused by exposure to resin-based composites to have a better understanding of the potential for clinical adverse effects. A more accurate understanding of the biological aspects of dental composite materials has been found after studying parameters like glutathione depletion, oxidative stress, genotoxicity, and immunomodulatory key effects in various cell culture models. Using omics-based approaches allow for a broader and non-specified search of changes caused by methacrylate exposure. Defense mechanisms and adaption are observed in cells exposed to monomer concentrations relevant to clinical exposure. The above-mentioned methods are the foundations for modified testing strategies. The clinical relevance of most available in vitro endpoint tests is of limited relevance for the patient. Research focusing on molecular mechanisms has given new insight into methacrylate toxicity in exposed cells. Using this knowledge from mechanistic studies to develop standardized in vitro biocompatibility tests will likely improve their clinical relevance.